A mechanical model to describe the vibroacoustic behaviour of elastomeric engine mounts for electric vehicles. (October 2020) - Lion, A.; Johlitz, M.
Highlights: A lumped mass approach and a continuous one represent the dynamics of engine mounts. Linear viscoelasticity with fractional derivatives describes the behaviour of the elastomer. The lumped mass approach approximates the continuous one with high accuracy. Cutting forces between mount, structure and engine are computed by formulae in closed form. Abstract: To develop well-adapted engine mounts for electric vehicles, it is essential to consider the propagation of structure-borne sound in the elastomer part of the bearing. Its transfer path leads from the vibrating engine via the elastomer to the body of the car. Since most of the electric vehicles possess neither manual nor automatic transmissions, the rotational speed of the engine is proportional to the driving velocity of the car. Since typical driving velocities are between 2 m/s and 60 m/s and the wheel circumferences of passenger cars are about 2 m, the rotational speed of the wheels is between 1 Hz and 30 Hz. Using a constant gear reduction with a ratio of 1/10, the rotational frequency of the engine is between 10 Hz and 300 Hz. If the electric engine is mechanically unbalanced, which is frequently the case, excitations with frequencies between 10 Hz and 300 Hz develop. The internal design of electric engines causes cogging torques and torque ripples whose frequency content contains multiples of the rotational frequency. In this essay, two mechanical models for elastomer mounts are developed which are applicable in such situations. In order to take the eigenmodes of the elastomer part into account, a number of single masses, connected via viscoelasticity elements, represents the flexible part of the mount. The frequency range of interest determines the number of the masses and the dynamic mechanical behaviour of the elastomer the material parameters of the viscoelasticity elements. For comparison, a continuous model is also developed. Both models are formulated in the time domain and are then transferred to the frequency domain. Simulations show the applicability of both approaches to understand and to enhance the dynamic behaviour of rubber bearings for electric vehicles.